2018
DOI: 10.1186/s13024-018-0254-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification and therapeutic modulation of a pro-inflammatory subset of disease-associated-microglia in Alzheimer’s disease

Abstract: BackgroundDisease-associated-microglia (DAM) represent transcriptionally-distinct and neurodegeneration-specific microglial profiles with unclear significance in Alzheimer’s disease (AD). An understanding of heterogeneity within DAM and their key regulators may guide pre-clinical experimentation and drug discovery.MethodsWeighted co-expression network analysis (WGCNA) was applied to existing microglial transcriptomic datasets from neuroinflammatory and neurodegenerative disease mouse models to identify modules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
383
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 316 publications
(406 citation statements)
references
References 70 publications
(130 reference statements)
21
383
2
Order By: Relevance
“…Compared with normal microglia the disease‐associated microglia progressively increase lipid metabolism and expression of phagocytic genes, and are specifically localized around AD plaques, thereby engulfing neurotoxic proteins and protecting against neurodegenerative diseases (Keren‐Shaul et al, ). However, recent discoveries using unbiased weighted co‐expression network analysis have shed light on another distinct pro‐inflammatory subpopulation of disease‐associated microglia in the context of AD (Rangaraju et al, ).…”
Section: Subsets Of Microglia: More Than Pro‐inflammatory and Immunormentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with normal microglia the disease‐associated microglia progressively increase lipid metabolism and expression of phagocytic genes, and are specifically localized around AD plaques, thereby engulfing neurotoxic proteins and protecting against neurodegenerative diseases (Keren‐Shaul et al, ). However, recent discoveries using unbiased weighted co‐expression network analysis have shed light on another distinct pro‐inflammatory subpopulation of disease‐associated microglia in the context of AD (Rangaraju et al, ).…”
Section: Subsets Of Microglia: More Than Pro‐inflammatory and Immunormentioning
confidence: 99%
“…Currently, it is still unknown whether other disease‐associated microglia subsets in different neurological disorders exist or not, or indeed whether specific subtypes are common to several neurological disease states. However, we are optimistic that further studies employing comprehensive combined transcriptome, proteomic and metabolomic approaches will define a wider spectrum of microglia subsets in different neurological disorders and facilitate targeting microglia with unprecedented precision (Haimon et al, ; Rangaraju et al, ). Thus further studies are warranted to characterize the scope of intrinsic mechanisms of disease‐associated microglia during diverse disease conditions.…”
Section: Subsets Of Microglia: More Than Pro‐inflammatory and Immunormentioning
confidence: 99%
“…Based on single cell RNAseq data, homeostatic microglia adopt distinct disease‐associated‐microglia (DAM) profiles in aging and chronic neurodegenerative diseases (Keren‐Shaul et al, ; Orre et al, ; Wang et al, ). DAM also appears to be a heterogeneous group of cells and we recently identified distinct pro‐inflammatory DAM and anti‐inflammatory DAM subsets within DAM (Rangaraju, Dammer, et al, ; Sarlus & Heneka, ). Flow cytometry studies confirmed that among CD11c + DAM, distinct CD44 + , and CXCR4 + subsets exist, and pharmacologic studies demonstrated that these sub‐profiles can be selectively modulated in‐vivo (Rangaraju, Dammer, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…DAM also appears to be a heterogeneous group of cells and we recently identified distinct pro‐inflammatory DAM and anti‐inflammatory DAM subsets within DAM (Rangaraju, Dammer, et al, ; Sarlus & Heneka, ). Flow cytometry studies confirmed that among CD11c + DAM, distinct CD44 + , and CXCR4 + subsets exist, and pharmacologic studies demonstrated that these sub‐profiles can be selectively modulated in‐vivo (Rangaraju, Dammer, et al, ). Although signature genes highly expressed by these microglial states and transcriptional regulators of microglial development and survival (PU.1, MAFB, SALL1, IRF8) are now known (Buttgereit et al, ; Kierdorf et al, ; Koshida, Oishi, Hamada, & Takahashi, ; Koso et al, ), the key upstream regulators of homeostatic, pro‐inflammatory DAM and anti‐inflammatory DAM transcriptional programs have not been identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation